HUBUNGAN KUALITAS TIDUR DENGAN KEBUGARAN JASMANI SISWA SEKOLAH DASAR NEGERI 13 SUNGAI PISANG - Anastasya Inayah Nabila P; Miftah Irrahmah; Endrinaldi Endrinaldi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Sleep quality is a fundamental human need crucial for physical health and cognitive function, particularly for school-aged children in their developmental phase. This study aims to determine the relationship between sleep quality and physical fitness levels among students at State Elementary School (SDN) 13 Sungai Pisang. The method employed was an observational analytic study with a cross-sectional design. The sample consisted of 58 students from grades IV and V, selected using a total sampling technique. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while physical fitness was assessed through the Indonesian Physical Fitness Test (TKJI). The results showed that the majority of respondents had good sleep quality (58.6%) and a moderate level of physical fitness (65.5%). Based on the chi-square statistical test, a p-value of 0.750 (p > 0.05) was obtained, indicating no statistically significant relationship between sleep quality and physical fitness among students at SDN 13 Sungai Pisang. Nonetheless, maintaining good sleep quality remains vital to support a child's overall health. Further research is needed to explore other factors, such as daily physical activity and nutrition, that may influence physical fitness within this school environment